Euroland's trade with the rest of the world: An SNA-based estimation - Hubert Strauß (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper presents an estimation of Euroland's foreign trade with the rest of the world based on the exports and imports of the eleven member states of the European Monetary Union according to their Systems of National Accounts (SNA). In order to isolate the trade with the rest of the world from intra- European trade flows, the share of intra-trade is derived from customs statistics. Once the time series are constructed, real exports are regressed on indexes of industrial production abroad and the real external value of the ecu - both calculated with respect to the 20 most important trading partners - using an error correction model. The estimation results are used to forecast Euroland's exports in 1998 and 1999.
Keywords: E32; F41; 330; Ecu; Euro; error correction model; export forecast; intra-European trade; real external value; Außenwirtschaft; Europäische Wirtschafts- und Währungsunion; Export; Prognose; EU-Staaten